If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + 5x + 11 = -2x + 5 Multiply x * x x2 + 5x + 11 = -2x + 5 Reorder the terms: 11 + 5x + x2 = -2x + 5 Reorder the terms: 11 + 5x + x2 = 5 + -2x Solving 11 + 5x + x2 = 5 + -2x Solving for variable 'x'. Reorder the terms: 11 + -5 + 5x + 2x + x2 = 5 + -2x + -5 + 2x Combine like terms: 11 + -5 = 6 6 + 5x + 2x + x2 = 5 + -2x + -5 + 2x Combine like terms: 5x + 2x = 7x 6 + 7x + x2 = 5 + -2x + -5 + 2x Reorder the terms: 6 + 7x + x2 = 5 + -5 + -2x + 2x Combine like terms: 5 + -5 = 0 6 + 7x + x2 = 0 + -2x + 2x 6 + 7x + x2 = -2x + 2x Combine like terms: -2x + 2x = 0 6 + 7x + x2 = 0 Factor a trinomial. (6 + x)(1 + x) = 0Subproblem 1
Set the factor '(6 + x)' equal to zero and attempt to solve: Simplifying 6 + x = 0 Solving 6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + x = 0 + -6 x = 0 + -6 Combine like terms: 0 + -6 = -6 x = -6 Simplifying x = -6Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {-6, -1}
| 0.5x+2=6 | | 5q+29=14 | | x*x-3x+6=10 | | 2+3m=-22 | | -5u+3=-4u | | -4(w-4)=-9w+6 | | 3u+7(u+2)=-16 | | 1.33x-5=23 | | xsquared=8 | | -3r-14=-4-5r | | 121x= | | -0.25x-19=1 | | 4(c-6)=(c+2) | | 5h-14=16+4h | | 50+3y=-7y | | 2x+6-7x=21 | | x*x-4x-32=0 | | 17x+3=139 | | 22(2-d)+9=198 | | -2y=3x+10 | | 33x+2880= | | 5+3(s-3t)=0 | | 6p-4=12p+8 | | Df+10=3ford | | 2(n+2)=-11 | | 3(x-5)-8=1-(1x-4) | | -12=6p | | 6p=12p+12 | | 2(2x+3)=-4+2(2x+5) | | 8+5(x+3)+7x= | | log(2x+3)=3 | | r=780d+-13dt |